Perilaku Remaja Awal yang Mengalami Sibling Rivalry dalam Keluarga di Kanagarian Koto Baru III Jorong - Anggraini, Putri Nadila; Rahmi, Alfi (ARZUSIN, 2023)
Aggressive behavior of early adolescents who experience sibling rivalry can grow in families with more than one child as stated by Bakwin H that sibling competition is more intense in small families (families with fewer children) compared to families with many children. . The aim is to find out the behavior of early adolescents who experience sibling rivalry in the family at Kanagarian Koto Baru III, Jorong. The research method is descriptive qualitative, key informants are 5 early adolescents who experience sibling rivalry and supporting informants 5 parents of early adolescents who experience sibling rivalry in the family. Data collection techniques through observation and interviews. Data analysis techniques with data reduction, data display, and data verification. The validity of the data used with data triangulation with source triangulation. The results of the study: 1) Verbal is a form of negative behavior in the form of words or verbally with the aim of hurting the victim (ridicule, insult, and yell). 2) Physical is a form of negative behavior in the form of physical assault aimed at injuring, harming, injuring, or damaging other people's objects (hitting, kicking, pushing, biting, and throwing), 3) Expression of anger is a form of behavior that its nature is hidden in the feelings of other people but the effect can be seen in actions that hurt other people (anger and annoyance). 4) Hostility is an invisible behavior, namely negative attitudes or feelings towards other people (jealousy and envy).